Evaluasi Kepuasan Pelanggan Terhadap Penggunaan SPKLU Wilayah Kerja PLN Unit Induk Distribusi Jawa Timur - Muhamad Akbar; Iwa Garniwa (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
The transition to electric vehicles is an important priority in efforts to reduce carbon emissions and achieve Indonesia's net zero emission target by 2060. However, the low utilization rate of Public Electric Vehicle Charging Stations (SPKLU), especially in East Java, indicates a gap between infrastructure availability and actual use by the community. This study aims to evaluate customer satisfaction with the use of SPKLU by reviewing factors of reliability, responsiveness, and service assurance. The research method uses a mixed methods approach, with a quantitative survey of 153 respondents who use electric cars in East Java and a qualitative approach through in-depth interviews with three informants. Quantitative analysis was conducted using Partial Least Square (SmartPLS 3.0), including validity, reliability, and hypothesis testing. The results show that SPKLU service quality (Service Quality) has a significant effect on Switching Intention (P Value = 0.000 <0.05) and subsequently SPKLU Users influence the intention to switch to electric cars (P Value = 0.014 <0.05). The t-statistic for the effect of Service Quality on Switching Intention was 3.84 (>1.96), and the effect of SPKLU Use on Switching Intention was 2.47 (>1.96). Qualitative analysis revealed that limited charging units, long waiting times, technical disruptions, and lack of staff support were the main barriers to SPKLU utilization. Triangulation results also indicated the need for strategic placement of SPKLUs in strategic locations and improved application and field service reliability. This study concluded that user satisfaction with SPKLU services plays a crucial role in driving electric vehicle adoption.